1997
DOI: 10.1086/593694
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppression in Paracoccidioidomycosis: T Cell Hyporesponsiveness to TwoParacoccidioides brasiliensisGlycoproteins that Elicit Strong Humoral Immune Response

Abstract: To assess human cellular immune response to paracoccidioidomycosis (PCM), lymphocyte proliferative responses to purified antigens from Paracoccidioides brasiliensis were determined in healthy persons previously infected by the fungus (positive donors), in healthy noninfected persons (controls), and in PCM patients. Affinity-purified gp70 and gp43, the two major antigens in humoral immune responses, were used. Both induced lymphocyte proliferation (gp43 species-specific) in positive donors but not in controls; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
58
0
20

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 10 publications
5
58
0
20
Order By: Relevance
“…The juvenile or acute form of the disease affects young adults of both sexes, is usually severe, and induces profound anergy of DTH reactions. Their lymphocytes behave as Th2 cells due to the enhanced secretion of IL-4, IL-5, and IL-10 [3,4]. The most common form of PCM, the adult form, has a chronic evolution and preferentially affects male individuals.…”
Section: Introductionmentioning
confidence: 99%
“…The juvenile or acute form of the disease affects young adults of both sexes, is usually severe, and induces profound anergy of DTH reactions. Their lymphocytes behave as Th2 cells due to the enhanced secretion of IL-4, IL-5, and IL-10 [3,4]. The most common form of PCM, the adult form, has a chronic evolution and preferentially affects male individuals.…”
Section: Introductionmentioning
confidence: 99%
“…These studies showed that the nature of the cellular immune defect was predominantly antigen-specific [21,22]. Decreased immune responses to challenges with Pb-unrelated microbial antigens were probably a consequence of the impairment of the general status of the patients, instead of an intrinsic defect of the immunity of PCM patients [14,16].…”
mentioning
confidence: 99%
“…In disagreement with some studies, but in agreement with others, we observed that the majority of the patients with PCM presented overall adequate T cell responses to mitogens (and to a Pb-unrelated fungal antigen). These studies are summarized in Table 1 [9][10][11][12][13][14][15][16][21][22][23][24][25][26].…”
mentioning
confidence: 99%
“…Specific T-cell-mediated immune responses play a fundamental role in the resistance to P. brasiliensis. Compared to individuals with localized disease, patients with systemic PCM display several defects in cellular immunity characterized by impaired in vivo delayed type hypersensitivity reactivity, alterations in the ratio of CD4 ϩ /CD8 ϩ cells, an imbalance in cytokine levels, and a depressed in vitro T-cell proliferation to fungal antigens (2,5,6,7,11,37,38).…”
mentioning
confidence: 99%